2015
DOI: 10.1080/07391102.2015.1046934
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin specifically binds to the human calcium–calmodulin-dependent protein kinase IV: fluorescence and molecular dynamics simulation studies

Abstract: Calcium-calmodulin-dependent protein kinase IV (CAMK4) plays significant role in the regulation of calcium-dependent gene expression, and thus, it is involved in varieties of cellular functions such as cell signaling and neuronal survival. On the other hand, curcumin, a naturally occurring yellow bioactive component of turmeric possesses wide spectrum of biological actions, and it is widely used to treat atherosclerosis, diabetes, cancer, and inflammation. It also acts as an antioxidant. Here, we studied the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…(Table 2). These results are consistent with curcumin, a natural anticancer molecule used as a positive control in this study [25]. It is noteworthy that β-carotene has a significant anticancer activity against hepatic cancer cell line, which bears lowest IC 50 value (41.52 μM) as shown in Fig 4B. …”
Section: β-Carotene Shows Anti-cancerous Activitysupporting
confidence: 93%
See 1 more Smart Citation
“…(Table 2). These results are consistent with curcumin, a natural anticancer molecule used as a positive control in this study [25]. It is noteworthy that β-carotene has a significant anticancer activity against hepatic cancer cell line, which bears lowest IC 50 value (41.52 μM) as shown in Fig 4B. …”
Section: β-Carotene Shows Anti-cancerous Activitysupporting
confidence: 93%
“…As CAMKIV is the responsible factor for neurodegenerative diseases and varieties of cancer, it could be considered a new target for the structure-based drug designing [25,26]. STO609, KN-93 [27] and KN-62 [28] are reported kinase inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…MD simulations can track system behavior and understanding of protein folding (Ubaid-Ullah et al 2014;Haque et al 2015;Naiyer et al 2015). These methods are used to investigate the structure, dynamics and thermodynamics of biological molecules (Anwer et al 2015;Hoda et al 2015;Naz et al 2015). In explicit conditions, all atoms of a protein and surrounding water molecules move in a series of time steps.…”
Section: Molecular Dynamic Simulationsmentioning
confidence: 99%
“…However, hesperidin did not show any growth‐inhibiting effect on HEK293 cells even up to > 200 μM concentration (Figure ), demonstrating its nontoxic nature against normal cells. Likewise, we have used a natural anticancer molecule, that is, curcumin as a positive control in this study (data not shown) . Collectively, these results indicate that hesperidin may possess antiproliferative activity and inhibits the HepG2 and SH‐SY5Y cells proliferation.…”
Section: Resultsmentioning
confidence: 72%